Klasifikasi Loayalitas Pelanggan Berdasarkan Perilaku Konsumen Menggunakan Analsisis Diskriminan - Auffrely Aris Nissa; Bilqis Agtari; Halimah Dinaya Putri; Sunita Dasman (CV. ITTC INDONESIA, 2026)
This study aims to classify customer loyalty of the Tokopedia e-commerce platform based on consumer behavior variables using a discriminatory analysis method. The data used is data sourced from the company's annual report, customer satisfaction survey published by Nielsen Indonesia in 2023, and aggregate transaction data used including purchase frequency, average transaction value, customer satisfaction level, recommendation behavior, and repeat order frequency. The dependent variables are the classifications of loyalty, loyal and disloyal. Data management uses SPSS. The results of the box's M test showed similarity in the variance-covariance matrix between the groups (p = 0.312 > 0.05). The discriminant function that was formed significantly differentiated the two groups (Wilks' Lamda = 0.187, p < 0.001) with a classification accuracy rate of 90.0%. The variable of purchase frequency and repeat orders is the most dominant variable in distinguishing customer loyalty groups